Reshoring within the EU - Billinton, Christian Svend Roy (2022)
The global economy is going through a tremendous shift with the ongoing Covid-19 crisis building protectionist sentiments towards deglobalization. This paper analyzes the reshoring phenomenon within the European Union, considering its developments and implication. The report compares the cause and effects of reshoring and interprets its present state in the EU to describe the phenomenon. The study utilizes the results of past studies and monitors of reshoring in the EU, such as the European Manufacturing Survey and the Eurofond Reshoring Monitor, to draw conclusions. Also, the implications of year-over-year changes in Input tables are used to distinguish the presence of reshoring in Europe. The study presents an overall analysis of reshoring. The results are of a two-sided view that weighs the reality against the desires of protectionism during times of upheaval.